Karriärens kropp - Salomonsson, Karin (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
In connection with the research project Cultural aspects of labour market segregation I have been studying job-advertisments in newspapers and on the Internet, analysing these as one of the more important billboards of the new economy. Here we see key symbols of the new economical era culturally negotiated and translated into terms of flexibility, flow, team-work, projects, commitment and attitude. Especially I find the illustrations and personifications of successful employees interesting. Here we are introduced to some emblematical icons of a new way to imagine and represent work — young, beautiful, smart and creative people, having fun at work. Recently a change seems to have taken place in favour of choosing pictures of "ordinary" people — preferably with the right diversity mix — instead of white, middle class males dressed in silk ties. In the article I give a few possible answers to this, the most general being a shift in rhetoric from the careerist to the career itself. In a society formed by postsocial relations it is culturally just as accepted to have a passionate relationship with your career as with your beloved.